"The i-th bit of E is obtained by taking the i-th bit of P, and xoring it with the product of the 1st bit of K and the 1st bit of P, and further xoring it with the product of the 2nd bit of K and the 2nd bit of P..." is what was contemplated.

]]>With the example from the logs: K=(0,1,0,1) P=(1,1,1,0) and E(2)=P(2) xor P(3) xor P(1) = 1 xor 1 xor 1 = 1 but with the formula above it would be E(2)= P(2) xor 0*P(1) xor 1*P(2) xor 0*P(3) xor 1*P(4) = P(2) xor P(2) xor P(4) = 1 xor 1 xor 0 = 0 .

]]>